Comment pense le jeu vidéo ? - Martin RINGOT (Conserveries Mémorielles)
Videogames are interactive works, which means that their meaning is actualized when the software is played. With the interactive loop, the player contributes to reorganize in an always new way the different narrative elements, but it is above all the gameplay which allows the videogames to produce a constant thought they let the interactor get thanks to a feedback.